2021
DOI: 10.1097/mat.0000000000001362
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hemoadsorption in Patients With Severe Intoxication Requiring Extracorporeal Cardiopulmonary Support—A Case Series

Abstract: Drugs intoxications often lead to severe vasoplegia and cardiogenic shock, and VA-ECMO represents a viable therapy option. However, as cardiopulmonary support is not contributing to the removal of the causal agent from the blood, detoxification by a new hemoadsorption device (CytoSorb) could represent a potential therapeutic tool due to its highly efficient elimination capacity of endogenous but also exogenous hydrophobic substances for which otherwise no effective antidote exist. In this case series, four ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 18 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Still, we find our decision to use the adsorber justified based on the critical situation and the lack of other alternatives. Generally, more and more reports on the use of CytoSorb in intoxications are meanwhile available and the reported cases do not only include those, in which complications like, for example, shock states were addressed with the therapy, 10 but also those, in which, similar as in our setting, direct detoxification was targeted 11 …”
Section: What Is New and Conclusionmentioning
confidence: 98%
“…7 So far 13 publications, including 17 patients have reported on the use of CytoSorb therapy in various intoxication settings (see Table 1), with the largest experience to date originating from the Charite Hospital in Berlin, Germany. 8 In this case series Zickler et al describe 4 anecdotal cases of acute intoxication (anti-hypertensives amlodipine and bisoprolol as well as the antidepressant amitriptyline) requiring Veno-Arterial (VA) ECMO) support used for extracorporeal cardiopulmonary resuscitation after intoxicationinduced out-of-hospital cardiac arrest (OHCA). 8 All patients were additionally treated with renal replacement therapy with CytoSorb treatment ranging from 1 to 7 days.…”
Section: Commentmentioning
confidence: 99%
“…8 In this case series Zickler et al describe 4 anecdotal cases of acute intoxication (anti-hypertensives amlodipine and bisoprolol as well as the antidepressant amitriptyline) requiring Veno-Arterial (VA) ECMO) support used for extracorporeal cardiopulmonary resuscitation after intoxicationinduced out-of-hospital cardiac arrest (OHCA). 8 All patients were additionally treated with renal replacement therapy with CytoSorb treatment ranging from 1 to 7 days. In these patients combined treatment was consistently associated with a dramatic decline in drug levels during treatment of all the overdosed drugs.…”
Section: Commentmentioning
confidence: 99%